2005
DOI: 10.1897/04-261r.1
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic toxicity of mercury to early life stages of the rainbow mussel, Villosa iris (Bivalvia: Unionidae)

Abstract: Mercury (Hg) contamination is receiving increased attention globally because of human health and environmental concerns. Few laboratory studies have examined the toxicity of Hg on early life stages of freshwater mussels, despite evidence that glochidia and juvenile life stages are more sensitive to contaminants than adults. Three bioassays (72-h acute glochidia, 96-h acute juvenile, and 21-d chronic juvenile toxicity tests) were conducted by exposing Villosa iris to mercuric chloride salt (HgCl2). Glochidia we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
2
31
0
1
Order By: Relevance
“…Revisions are planned to the ASTM methods [1,7] and to USEPA method [2] to further describe biomass as a toxicity endpoint that can be used to integrate combined effects of a treatment on survival or weight of test organisms. Previous water or sediment toxicity testing conducted with juvenile freshwater mussels has demonstrated that growth (reported as dry wt or length) tends to be a more sensitive endpoint relative to survival [9,11,[15][16][17]30]. Mussels may be avoiding exposure to contaminants by valve closure, but this avoidance may come at a cost of reduced feeding and reduced growth.…”
Section: Relative Species and Endpoint Sensitivitymentioning
confidence: 99%
“…Revisions are planned to the ASTM methods [1,7] and to USEPA method [2] to further describe biomass as a toxicity endpoint that can be used to integrate combined effects of a treatment on survival or weight of test organisms. Previous water or sediment toxicity testing conducted with juvenile freshwater mussels has demonstrated that growth (reported as dry wt or length) tends to be a more sensitive endpoint relative to survival [9,11,[15][16][17]30]. Mussels may be avoiding exposure to contaminants by valve closure, but this avoidance may come at a cost of reduced feeding and reduced growth.…”
Section: Relative Species and Endpoint Sensitivitymentioning
confidence: 99%
“…Several studies found the larval glochidia of certain unionid species including V. iris are more sensitive than juveniles to various toxicants (Keller and Ruessler 1997;Augspurger et al 2003;Valenti et al 2005). Physiological advantages of juvenile mussels may also contribute to their tolerance of toxicological stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile mussels are better adapted to avoid toxicants due to thicker shells, compared to glochidia, which have thinner, more permeable shells (Hoggarth and Gaunt 1988). Additionally, juvenile stage mussels may also be able to alter their metabolism, reducing filtration rates and closing their valves for extended periods of time (Valenti et al 2005), something neither C. dubia or glochidial stage mussels can do. Although V. iris may have been more tolerant to both the brine discharge and reference test exposure to sodium chloride, the mussel's physiology and ability to stay closed for extended periods of time may have contributed to the more tolerant results obtained from the acute tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the current researchers conducted ecotoxicology studies on these organisms because of their sensitivity to a variety of environmental disturbance, ease of collection and handling, and/or the lack of reliable information to support conservation and management. About their employment to assess genotoxicity and their use as animal tests (Makala and Oikari, 1990; Mersch and Beauvais, 1997), Valenti et al (2005) reported that the results provided by experimental toxicity tests are critical for their conservation. Numerous laboratory studies have been conducted on freshwater mussels in order to understand the role of contaminants in the decline of the populations (Valenti et al, 2005; Ingersoll et al, 2006).…”
Section: Ecotoxicologymentioning
confidence: 99%